Identification of Characteristics of Traditional Acehnese Architecture at SMEA Premium Coffee Shop in Banda Aceh - Armelia Dafrina; Fidyati Fidyati; Muthmainah Muthmainah; Mochamad Ari Saptari (Electronic Journal of Education, Social Economics and Technology, 2025)
The city of Banda Aceh has experienced significant development in building infrastructure, particularly in the proliferation of coffee shops. Many open spaces have been repurposed into coffee shops, and this transformation has also brought significant changes to the function and form of the traditional Acehnese house, Acehnese House (Rumoeh Aceh), which is now being repurposed into commercial spaces such as coffee shops. This transformation affects both the function and meaning of the buildings in response to evolving needs.  This study aims to examine characteristics of traditional Acehnese architecture as applied to coffee shops in Banda Aceh. The analysis is based on Hadjad’s theoretical framework, which assesses the characteristics of traditional Acehnese architecture through 12 elements: stilted structure, roof, columns, walls, space, under floor space, openings, ornaments, orientation, house height, color, and materials. The results of the study show that these coffee shops have retained core elements of Rumoh Aceh, such as the stilted house form, wooden materials, and traditional ornaments, despite undergoing design and functional adaptations for commercial purposes. This study highlights that the application of traditional architecture in public spaces can serve as a medium for cultural education while strengthening local identity amidst the wave of modernization.